Determinants of Stunting Prevalence: Health Expenditure, Women Education, and Protein Consumption - Nurissalsabila, Ningrum; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
Stunting remains a chronic nutritional problem with a high prevalence in East Nusa Tenggara Province (NTT). This study aims to analyze the effects of health function expenditure function, female education levels, and protein consumption on stunting prevalence in NTT during the 2017–2023 period using district/city panel data. The results indicate that health function expenditure function and female education have a significant impact on reducing stunting prevalence, while protein consumption does not show a statistically significant partial effect. These findings emphasize that stunting reduction requires effective health service delivery and maternal educational capacity, rather than solely increased nutritional consumption. Optimizing health expenditure function and improving female education are therefore crucial strategies for accelerating stunting reduction in NTT.